Graphic Design as a Universal Language: Symbols and Codes in the Vision of Gio Ponti (diségno, 2025)
Graphic design was a tool for Gio Ponti to synthesise his design and communication, bringing together art, architecture, and design in a consistent visual language. This study looks at the role of graphic design in his work, highlighting its function not only as a means of representation but also as an independent code capable of conveying complex concepts. Through an iconographic and semiotic analysis of his works, the influences of the Bauhaus, Futurism and Italian Rationalism are explored, contributing to the definition of his graphic style, characterised by modularity, geometry and an innovative use of colour. The research also investigates the relationship between editorial graphics, architectural production and industrial design, demonstrating how Ponti’s style has become a constantly evolving visual matrix. Finally, the potential for mutation of his language in the contemporary context is analysed through digital graphic experimentation and new branding and interactive design applications. The article highlights how graphic design for Ponti was not merely a means of representation, but a form of visual thinking capable of transcending eras and contexts, confirming itself as a fundamental reference point for contemporary design.
Keywords: graphic design; visual language; Gio Ponti; symbols; geometry